2003
DOI: 10.1186/1472-6882-3-7
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorating effect of microdoses of a potentized homeopathic drug, Arsenicum Album, on arsenic-induced toxicity in mice

Abstract: BackgroundArsenic in groundwater and its accumulation in plants and animals have assumed a menacing proportion in a large part of West Bengal, India and adjoining areas of Bangladesh. Because of the tremendous magnitude of the problem, there seems to be no way to tackle the problem overnight. Efforts to provide arsenic free water to the millions of people living in these dreaded zones are being made, but are awfully inadequate. In our quest for finding out an easy, safe and affordable means to combat this prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
48
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 29 publications
5
48
0
Order By: Relevance
“…[43][44][45] The intraperitoneal route was chosen in an attempt to avoid the potential confounding factors on As 2 O 3 absorption through the gastrointestinal tract and to compare parenteral arsenic effects with previous reports in the literature. 46,47 We showed that the addition of trolox to As 2 O 3 given to mice bearing P388 lymphoma cells significantly increased their survival time. It has been reported, using the same model, that ascorbic acid enhanced antitumor properties of As 2 O 3.…”
Section: Discussionmentioning
confidence: 94%
“…[43][44][45] The intraperitoneal route was chosen in an attempt to avoid the potential confounding factors on As 2 O 3 absorption through the gastrointestinal tract and to compare parenteral arsenic effects with previous reports in the literature. 46,47 We showed that the addition of trolox to As 2 O 3 given to mice bearing P388 lymphoma cells significantly increased their survival time. It has been reported, using the same model, that ascorbic acid enhanced antitumor properties of As 2 O 3.…”
Section: Discussionmentioning
confidence: 94%
“…Simultaneous feeding of both SA and LA caused an elevation of about 1 and 2 folds in AST and ALT activities respectively ( Table 2). The induction of AST and ALT activities following exposure to As has been documented (Mallick, et al, 2003). Basic histopathological analysis of the organs from the rats after sacrifice showed that rats fed simultaneously with SA and LA had mild infiltrative hemorrhage in their lungs.…”
Section: Discussionmentioning
confidence: 97%
“…A study on biochemical changes in the kidney of Labeo rohita intoxicated with arsenic found that FTIR study can be applied for toxicology [12]. As well a related study of ars alb 30C and ars alb 200 was said to be more effective [13]. Further studies were carried out that the ars alb contains ultra high dilution of Arsenic trioxide was re-equilibrate upregulated genes at the time of oxidate stress by brought back expression levels [14].…”
Section: Discussionmentioning
confidence: 99%